Analisis Perencanaan Waktu Pada Proyek Peningkatan Ruas Jalan Bulo-Bungin Di Kabupaten Enrekang - Muh Agung Dewa Saputra D; Natsir Abduh; Satriawati Cangara (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
This study examines the "Review of Time and Labor Schedule Planning for the Bulo-Bungin Road Improvement Project in Enrekang Regency" which has the aim of knowing the duration of time and how much optimal labor is needed or required in the Bulo-Bungin road improvement project in Enrekang Regency. This research uses quantitative research to analyze data obtained from project sites and related documentation. The analysis method used in this research is Critical Path Method (CPM). Where Critical Path Method (CPM) is used to prioritize project activities or activities. The results showed that using the Critical Path Method to plan the project's time and labor schedule was more effective, because the duration of the work time was 8 days faster than before using the s-curve says it takes 140 days.